PENGARUH PERSEPSI KUALITAS PRODUK DAN LOYALITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG HANDPHONE BLACKBERRY PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS STIKUBANK SEMARANG - Mahendra Bayu Irawan, 09.05.51.0082 (Students Journal of Economic and Management, 2013)
The purpose of this study was to analyze the effect of perceived quality and brand loyalty to the Blackberry mobile phone repeat purchasing decisions. The population in this study were students of the Faculty of Economics, University Stikubank Semarang. The sample size used is based on the formula proposed by Taro obtained as many as 100 people. Sampling technique using purposive sampling. Data used in this study is primary data is data obtained directly from the original source. Analysis results can be concluded that: (a) Perceived quality has a positive effect on repeat purchasing decisions. The better the perceived quality blackberry phone, blackberry phone then repeat purchasing decisions will increase. (b) Brand loyalty has a positive effect on repeat purchasing decisions. The more loyal customers, the blackberry mobile phone repeat purchasing decisions will increase. Â Keywords: perceived quality, brand loyalty and repeat purchase decisions